ANALYSIS OF POLITENESS STRATEGIES USED IN THE PRINCESS DIARIES MOVIE - Himawati, Ulya; Talenta, Pratama Irwin; Lamik, Muhammad Munif (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2024)
Politeness is the idea of polite social behavior. It represents in through behaviors and the conversation. Someone is considered polite not only if he / she is able use proper language in a proper way. According to Brown and Levinson (1978), politeness is the acts that accounts for the redressing of the affronts to face posed by face-threatening acts to addressees. Therefore, politeness often regards as an action to lessen the face-threatening act. There are no rules how frequent politeness used in conversation, moreover, those who comes from higher status tend to speak in polite way. To them, being polite shows their high education status and maturity thinking. This condition shows in movies, one of which is the Princess Diaries movie. The main characters are royal family, therefore many polite dialogues shown. This study seeks kinds of politeness strategies used in the movie. Ten representative dialogues selected and analyzed to what strategies included. The analysis discussed using a table, grouped them into its strategies, followed by deep explanation. The dialogues grouped to four politeness strategies: positive, negative, bald on record (direct) and off-record (indirect), as stated by Brown and Levinson (1978). The result is 90% of the dialogues used politeness used by people who lives in royal environment, including their staffs. There is a tendency using positive politeness than negative politeness used by the royal. The movie also shows that off-record (indirectness) used to reject undesirable action done by someone.